Studi Tafsīr Jalālain di Pesantren dan Ideologisasi Aswaja - Kurdi Fadlal (Nun : Jurnal Studi Alquran dan Tafsir di Nusantara, 2016)
This article discusses Tafsi>r Jala>lain as a literature to process Aswaja ideologization in the pesantren milieu. It is the first Islamic literature introduced by Java-Muslim scholars in the institution. The motivation is not only technical (simple description) so that Indonesian Muslim can easily understand the Qur’anic interpretation, but also ideological one. To embed the ideology Tafsi>r Jala>lain were utilized because it describes ideological interpretation of Ahlus Sunnah wal Jamaah, the primary and selected ideology among figures of pesantren. About theology it refers to Asha’iran school and regarding fiqh (Islamic Jurisprudence) it points to Shafi’ian. There are two mothods to embed the ideology to the community of pesantren mil1ieu through Tafsi>r Jala>lain: First, orally, bandongan by reading or teaching it to the students. Second, literally, by translating the Tafsi>r into the local language (Indonesian, Javanese, Maduranese and Sundanese). In turn, Aswaja ideology was rooted in the pesantren and ascertained by Nahdlatul Ulama (NU) organization founded in 1926.